Medical education - competency based medical education - how far, how near - moving from rote learning to artificial intelligence - Challenges in medical education and preparing faculty to meet current and future challenges - part 3 - N.K. Gupta; Ayesha Ahmad; Uma Gupta (Al Ameen Medical College, 2024)
In last two manuscripts we discussed, Medical Education - competency based medical education - How far and how near - moving from rote learning to artificial intelligence part 1 [1] and Medical Education - competency based medical education - How far and how near - moving from rote learning to artificial intelligence part 2 - Preparing learners to meet future changes and challenges [2]. In this concluding article we will discuss challenges faced by faculties and ways and means to meet them for comfortable and reasonable achievements.